The Role of Job Satisfaction in Bridging Organizational Culture, Servant Leadership, Self Leadership, and Compensation with Employee Performance - Devi, Ardana Prakasita (Universitas Ciputra Surabaya, 2022)
Information technology is a set of tools that can help someone in working with information andperforming tasks related to information data processing. Business competition is increasingly following the development of this era, causing many companies faced with a situation where they must be able to overcome the problems they face quickly. Currently CV Inti Computer company located in the Kediri area is more likely to use information processing systems based on computer desktop applications because inaddition to providing convenience for users can also provide information quickly, relevant, timely,complete, understandable and proven truth. In connection with this matter how employees can work well with the role of job satisfaction in bridging organizational culture, servant leadership, self leadership, and compensation for employee performance. So with that in mind, this study aims to investigate the influenceof organizational culture, servant leadership, self leadership, and compensation to employee performance. Respondents in this study were 30 employees of CV Inti Computer. Data collection methods used were using a questionnaire and in analyzing the data using structural equation modelling analysis with partial least square. The results of this study indicate that there is a partially insignificant influence of organizational culture on employee performance, insignificant influence of servant leadership on job satisfaction, insignificant influence of servant leadership on employee performance, significant influence ofself leadership on job satisfaction, significant influence of self leadership on employee performance , the significant effect of compensation on job satisfaction, the significant effect of compensation on employee performance, and the significant effect of job satisfaction on employee performance.